STRIKING PEDAGOGICAL EQUILIBRIUM: TAILORING TEACHING APPROACHES TO MITIGATE STUDENT BURNOUT IN ISLAMIC BOARDING SCHOOL MANAGEMENT - Rahmatul Aziz Al Mursyidin; Hakim, Ahmad Muzakki (Universitas Nurul Jadid, 2023)
The purpose of this article is to discuss learning methods in pesantren in reducing student boredom through the yellow book. The yellow book is a learning literature that is typical of pesantren, understanding in learning the monotonous yellow book can cause students to feel bored in learning. Through this descriptive qualitative research, it is expected to be able to contribute reference knowledge about the yellow book learning strategy through active and creative teaching methods and styles in reducing student boredom. The result of this study is the trategi of learning the yellow book at the Lubbul Labib Islamic boarding school using two aspects of strategy including classical learning methods (sorogan and badongan), and the bahtsul masail method. The combination of these two aspects creates a dynamic and engaged learning atmosphere, motivating students to be actively involved in the learning process so as to overcome student boredom at Lubbul Labib boarding school.